Experimental and Quantum Chemical Studies of Nicotinamide-Oxalic Acid Salt: Hydrogen Bonding, AIM and NBO Analysis - Verma, Priya; Srivastava, Anubha; Tandon, Poonam; Shimpi, Manishkumar R. (Frontiers in Chemistry, 2022)
The computational modeling supported with experimental results can explain the overall structural packing by predicting the hydrogen bond interactions present in any cocrystals (active pharmaceutical ingredients + co-former) as well as salts. In this context, the hydrogen bonding synthons, physiochemical properties (chemical reactivity and stability) and drug likeliness behavior of proposed nicotinamide-oxalic acid (NIC-OXA) salt have been reportedby using vibrational spectroscopic signatures (IR and Raman spectra) and quantum chemical calculations. The NIC-OXA salt was prepared by reactive crystallization method. X-ray powder diffraction (XRPD) and differential scanning calorimetry (DSC) techniques were used for characterization and validation of NIC-OXA salt. The spectroscopic signatures revealed that (N7-H8)/(N23-H24) of pyridine ring of NIC, (C=O) and (C-O) groups of OXA were forming the intermolecular hydrogen bonding (N7-H8•••O5-C6), (N23-H24•••O2-C3), (C10-H22•••O1=C3), (C26-H38•••O4=C6), (N7-H8•••O1=C3) and (N23-H24•••O4=C6) in NIC-OXA salt. Additionally, quantum theory of atoms in molecules (QTAIM) showed that (C10-H22•••O1) and (C26-H38•••O4) are two unconventional hydrogen bonds present in NIC-OXA salt. Also, the natural bond orbital (NBO) analysis were performed to find the charge transfer interactions and revealed the strongest hydrogen bonds (N7-H8•••O5)/(N23-H24•••O2) in NIC-OXA salt. The frontier molecular orbitals (FMOs) analysis suggested more reactivity and less stability of NIC-OXA salt in comparison to NIC-CA cocrystal and NIC. The global and local reactivity descriptors were calculated and predicted that NIC-OXA salt is softer than NIC-CA cocrystal and NIC. From MESP of NIC-OXA salt, it is clear that electrophilic (N7-H8)/(N23-H24), (C6=O4)/(C3=O1) and nucleophilic (C10-H22)/(C26-H38), (C6-O5)/(C3-O2) reactive groups in NIC and OXA, respectively, neutralize after formation of NIC-OXA salt, confirm the presence of hydrogen bonding interactions (N7-H8•••O5-C6) and (N23-H24•••O2-C3). The Lipinski rule was applied to check the activeness of salt as orally active form. The results shed light on the several features of NIC-OXA salt which can further lead to improvement in the physicochemical properties of NIC.